2022
DOI: 10.3390/agronomy12112651
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Volatile Profiles of Six Industrial Hemp (Cannabis sativa L.) Cultivars

Abstract: Volatile organic compounds (VOCs) play an important role in plant ecology and can be useful in pest management. This work characterises, for the first time, the VOC emissions of six industrial hemp (Cannabis sativa L.) cultivars grown in New Zealand: CFX-2, CRS-1, Ferimon 12, Katani, Futura 75, and Finola. Volatiles emitted from flowers and foliage of eight-week-old plants were collected using a dynamic headspace sampling method and analysed using gas chromatography coupled to mass spectrometry. We assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…Several investigations have sought to increase cannabinoid content using JA or methyl-JA treatments on Cannabis flowers [ 154 ], leaves [ 155 ], or cell cultures [ 156 ] and have been met with mixed results. Studies that analyze oxylipin levels in Cannabis tissues or products have focused on volatiles from above-ground tissues [ 157 ], seeds [ 158 ], or seed oil [ 159 , 160 ] as components of their odor profiles. Recently, it was found that sex impacts the distinct oxylipin species that accumulate in the Cannabis flower.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have sought to increase cannabinoid content using JA or methyl-JA treatments on Cannabis flowers [ 154 ], leaves [ 155 ], or cell cultures [ 156 ] and have been met with mixed results. Studies that analyze oxylipin levels in Cannabis tissues or products have focused on volatiles from above-ground tissues [ 157 ], seeds [ 158 ], or seed oil [ 159 , 160 ] as components of their odor profiles. Recently, it was found that sex impacts the distinct oxylipin species that accumulate in the Cannabis flower.…”
Section: Discussionmentioning
confidence: 99%
“…References included in the compilation of data presented in this work include concentration and emission measurements of ecosystems or prevalent forest vegetation. This work does not include bodies of literature on the emissions of specific cultivated crops or on aromas or headspace of specific flowers or ornamental plants. Any works captured by these search terms in these bodies of literature are included in the references in the prior statement but not compiled or discussed further in the present work, although a cursory review suggests the complexity and variability of the chemical class are similar in these works as that will be shown in the present work.…”
Section: Methodsmentioning
confidence: 99%
“…Cannabis sativa L. produces a wide array of secondary metabolites, but it is also a prolific producer of Volatile Organic Compounds (VOCs) (22). One of the study reported the first analysis of Volatile Organic Compounds (VOCs) emitted from hemp, Cannabis sativa cultivars grown in New Zealand (22).…”
Section: Cannabis Sativa: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
“…Cannabis sativa L. produces a wide array of secondary metabolites, but it is also a prolific producer of Volatile Organic Compounds (VOCs) (22). One of the study reported the first analysis of Volatile Organic Compounds (VOCs) emitted from hemp, Cannabis sativa cultivars grown in New Zealand (22). This work characterises, for the first time, the Volatile Organic Compounds (VOCs) emissions of six industrial hemp (Cannabis sativa L.) cultivars grown in New Zealand: CFX-2, CRS-1, Ferimon 12, Katani, Futura 75, and Finola (22).…”
Section: Cannabis Sativa: Volatile Organic Compounds (Vocs)mentioning
confidence: 99%
See 1 more Smart Citation